2020
DOI: 10.1002/er.5902
|View full text |Cite
|
Sign up to set email alerts
|

Integrated SnSSe bulk and monolayer as industrial waste heat thermoelectric materials

Abstract: Summary New, nontoxic and earth‐abundant materials for heat‐energy interconversion are urgently required to mitigate the over‐reliance on finite fossil fuels supply. Herein, using ab initio quantum mechanical calculations and Boltzmann theory, optimization of thermoelectric performances instable, mechanically robustCm‐SnSSe and P3m1‐SnSeS phases was performed. These phases exhibit an intrinsically low thermal conductivity of ~1.00 W m−1 K−1 at room temperature. Beyond 400 K, both phases display satisfactory th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 47 publications
2
8
0
Order By: Relevance
“…Unlike graphene, our systems possessed a sandwiched structure (X−Sn−Y) with the space group of P 3 m 1, and they lacked both the inversion center and out-of-plane mirror symmetry. As can be found from Table 1 , the lattice constant ( ), the layer thickness ( ), and the bond length ( , ) increased with the radii of X and Y atoms, which are in good agreement with those reported previously [ 21 , 22 , 23 , 24 ]. If we focus on the difference ( ) between and , we found that was the largest for the Janus SnOSe, smallest for the SnSSe, with the SnOS in between.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Unlike graphene, our systems possessed a sandwiched structure (X−Sn−Y) with the space group of P 3 m 1, and they lacked both the inversion center and out-of-plane mirror symmetry. As can be found from Table 1 , the lattice constant ( ), the layer thickness ( ), and the bond length ( , ) increased with the radii of X and Y atoms, which are in good agreement with those reported previously [ 21 , 22 , 23 , 24 ]. If we focus on the difference ( ) between and , we found that was the largest for the Janus SnOSe, smallest for the SnSSe, with the SnOS in between.…”
Section: Resultssupporting
confidence: 91%
“…Using first-principles calculations, Yuan et al [ 20 ] found that the formation energies of Janus MnSTe, MnSeTe, MnSSe, and VSeTe can be comparable to those of the parents MnS 2 , MnSe 2 , MnTe 2 , VSe 2 , and VTe 2 . In addition, previous ab-initio studies confirmed the chemical, dynamical, and mechanical stability of Janus monolayer SnSSe, which exhibits promising optoelectronic properties for solar cells applications and can be also used as appealing industrial waste thermoelectric materials [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…49 If these factors are included in the estimation of lattice thermal transport, the temperature dependence of the κ L of M 3 Sb may be different from the above results, which indicates a potential limitation of the method used in the present calculation. 50 The lattice thermal conductivity results are shown in Figure 3, from which we can capture the following information: first, these alkali antimonide compounds have ultra-low lattice thermal conductivity with a value of 1.26, 0.63 and 0.52 Wm −1 K −1 of K 3 Sb, Rb 3 Sb and Cs 3 Sb at a temperature of 300 K, respectively, which is much smaller than the typical thermoelectric material PbTe (κ L 2 Wm −1 K −1 ) [51][52][53] and comparable to the cubic antiperovskites A 3 BO (A = K, Rb; B = Br, Au) (κ L 0.73-1.7 Wm −1 K −1 ), 37 Cm-SnSSe and P3m1-SnSeS (κ L 1.00 Wm −1 K −1 ), 54 57 and based on the ultra-low lattice thermal conductivity, these materials may exhibit good thermoelectric properties. We calculated their Seebeck coefficient, electrical conductivity and showed them in S3, and the results indicate that the Seebeck coefficients of these alkali antimonide compounds M 3 Sb are larger than that of thermoelectric materials such as Na-doped PbTe (S 0.3 mV/K), 58 Li 3 Bi (S 0.25 mV/K) 59 and BP bilayer (S 0.3 mV/K) 60 at the appropriate doping concentration.…”
Section: Resultsmentioning
confidence: 85%
“…With the fossil fuel supply decreases and the world energy demand increases, the search for sustainable and clean energy has become a crucial social issue in the 21 st century. 1,2 Over these years, thermoelectric (TE) materials have received widespread attention, and the combination of thermal and electrical as well as semiconductor properties of TE materials make them useful for using heat to generate electricity. TE materials have an important effect on solving the international energy shortage problem.…”
Section: Introductionmentioning
confidence: 99%